Egyetemi nyelvi képzés a Közép-Duna Menti Térségben - Koltai, Zoltán (Kultúratudományi Szemle, 2022)
University language training in the Middle Danube Region Zoltán Koltai The University of Pécs provided in 2021, in connection with the Paks II project, online English and Russian language learning, free of charge, for adults living or working in the settlements of the Middle Danube Region, or in the towns Bonyhád and Dombóvár. The aim of the programme was the preparation of the inhabitants or the labour force of the area for personal communication with the foreign employers and their family members arriving for the implementation of the Paks II investment. The implementation of the training took place with the involvement of language teachers provided by two faculties of the University of Pécs: the Faculty of Humanities and Social Sciences and the Faculty of Cultural Sciences, Education and Regional Development. The paper demonstrates the major steps of the organisational process of the programme, with special emphasis on the challenges related to online implementation, and also focuses on the achievements.